Computer tomography guided thoracoscopic resection of small pulmonary nodules in the hybrid theatre. - Ioannis Karampinis (Public Library of Science (PLoS), 2021)
Purpose Thoracic surgeons are currently asked to resect smaller and deeper lesions which are difficult to detect thoracoscopically. The growing number of those lesions arises both from lung cancer screening programs and from follow-up of extrathoracic malignancies. This study analyzed the routine use of a CT-aided thoracoscopic approach to small pulmonary nodules in the hybrid theatre and the resulting changes in the treatment pathway. Methods 50 patients were retrospectively included. The clinical indication for histological diagnosis was suspected metastasis in 46 patients. Technically, the radiological distance between the periphery of the lesion and the visceral pleura had to exceed the maximum diameter of the lesion for the patient to be included. A spiral wire was placed using intraoperative CT-based laser navigation to guide the thoracoscopic resection. Results The mean diameter of the lesions was 8.4 mm (SD 4.27 mm). 29.4 minutes (SD 28.5) were required on average for the wire placement and 42.3 minutes (SD 20.1) for the resection of the lesion. Histopathology confirmed the expected diagnosis in 30 of 52 lesions. In the remaining 22 lesions, 9 cases of primary lung cancer were detected while 12 patients showed a benign disease. Conclusion Computer tomography assisted thoracoscopic surgery (CATS) enabled successful resection in all cases with minimal morbidity. The histological diagnosis led to a treatment change in 42% of the patients. The hybrid-CATS technique provides good access to deeply located small pulmonary nodules and could be particularly valuable in the emerging setting of lung cancer screening.